Is the god of diamonds alone? The role of institutions in artisanal mining in forest landscapes, Congo Basin - Schure, J.; Ingram, V.J.; Tieguhong, J.C.; Ndikumagenge, C. (2011)
This paper examines the institutional framework of artisanal mining in the forests of the Sangha Tri-National Landscape (TNS) in the Congo Basin. Artisanal miners in Cameroon and the Central African Republic (CAR) commonly make sacrifices to their god of diamonds, to improve fortunes. This study looks into ‘the other forces’; institutions that play a role in shaping the sector and its outcomes. These institutions comprise formal and informal institutions at a local, national, regional and international level. Although artisanal miners in TNS benefit by gaining cash income, this activity also carries risks as income is highly disparate and environmental impacts in this priority forest conservation area are expected to increase due to the growing competition over land use. It was concluded from a literature review, interviews and site visits that informal arrangements dominate the sector, especially in Cameroon, leading to poor relations between officials and miners and meaning that miners have few rights and no voice. The current institutional setup is inadequate to deal with current and anticipated social and environmental issues. Future interventions need to take into account the existing (local) types of organization, vulnerable groups, the interests of multiple actors and the fact that most miners are experienced but combine mining with other activities, such as agriculture, fishing and harvesting forest products. African initiatives concerning ASM offer opportunities to Cameroon and CAR to collaborate with other countries to combat similar issues. A regional integrated approach of both the forest and mining sector would be especially relevant for trans-boundary agreements, such as concerning the TNS, to reinforce positive outcomes for the landscape and the area's population.